Biopatterning: Precise Protein Photolithography (P3): High Performance Biopatterning Using Silk Fibroin Light Chain as the Resist (Adv. Sci. 9/2017). Issue 9 (September 2017) - Liu, Wanpeng; Zhou, Zhitao; Zhang, Shaoqing; Shi, Zhifeng; Tabarini, Justin; Lee, Woonsoo; Zhang, Yeshun; Gilbert Corder, S. N.; Li, Xinxin; Dong, Fei; Cheng, Liang; Liu, Mengkun; et al.
Abstract : A wafer‐scale high resolution patterning of bio‐microstructures is achieved using precise protein photolithography. In article number1700191, the application of these micropatterned structures as cellular substrate for the successful spatial guidance of fetal neural stems cells using well‐defined silk fibroin light chain as the resist material is demonstrated by Tiger H. Tao and co‐workers.